Exploring science teachers’ readiness for deep learning implementation through teaching module analysis and lesson study - Yayuk Mulyati; Nasrunniati Dyahayu Anggi Winarni; Indra Fardhani; Erni Yulianti; H. Habiddin; S. Sugiyanto; Umi Fitriyati; Elisa Mariana Magnani; Erti Hamimi (Universitas Muhammadiyah Malang, 2026)
Background-This study examines junior high school science teachers’ readiness to implement deep learning (DL) within the Merdeka Curriculum through teaching module analysis, surveys, UbD-based workshops, and Lesson Study (LS). Objectives-The objectives of this study are: (1) to analyze the cognitive levels of learning objectives (LO) and their alignment with DL principles, and (2) to evaluate the development of teachers’ reflective practices through LS. Method-This study employed a mixed-methods approach, combining survey data from 22 teachers with qualitative analysis of teaching documents, classroom observations, and LS reflections. Results-The findings show that 77% of teachers designed lessons collaboratively and 45% developed relatively complete learning tools, although only 4% applied UbD principles. Analysis of 90 LOs indicates that 70.45% were categorized as lower-order thinking skills (LOTS), dominated by C2 (51.13%) and C3 (15.91%), while HOTS remained limited. The average alignment between assessment and LO reached ±89%, but was mostly structural rather than conceptual. LS implementation improved teachers’ awareness of alignment and reflective practices, particularly in LS-2. Conclusions-These findings indicate that teachers demonstrate emerging readiness for DL; however, continuous support is needed to strengthen conceptual alignment and meaningful learning design.